BOOKS RECENTLY PUBLISHED. - Little, Karen R.; Procell, James (Notes, 2012)
A bibliography is presented of music-related books including "Before Seattle Rocked: A City and Its Music" by Kurt E. Armbruster, "Technology and the Gendering of Music Education" by Victoria Armstrong, and "Perfect Lives: An Opera" by Robert Ashley.